(untitled) (Journal of Bangladesh Academy of Sciences, 2017)
Five plant extracts and two chemicals were evaluated against radial growth of five pathogenic fungi isolated from fresh vegetables of two varieties of Momordica charantia L. The isolated fungi were Aspergillus niger Van Tiegh, Curvularia brachyspora Boedijn, Fusarium Link, Rhizopus stolonifer (Ehrenb.:Fr.) Vuill and Trichoderma viride Pers.. Five plant extracts namely Allium sativum L., Azadirachta indicia A. Juss., Citrus limon (L.) Burm. f, Mangifera indica L. and Psidium guajava L. were evaluated for inhibiting growth of above mentioned fungi associated with the vegetable. Out of the five plant extracts, A. sativum showed complete radial growth inhibition of A. niger, C. brachyspora, Fusarium sp. and R. stolonifer at 15 and 20% concentrations. Azadirachta indica showed complete radial growth inhibition of C. brachyspora and Fusarium sp. Rhizopus stolonifer was completely inhibited by 15 and 20% concentration owing to leaf extract of A. indica and P. guajava. The same fungus was completely inhibited by M. indica at 20% concentration. Fusarium sp. was completely inhibited by C. limon at 20% concentration. Two chemicals, sodium bicarbonate and sodium chloride were used against the test pathogens and sodium bicarbonate showed complete inhibition of radial growth of A. niger, C. brachyspora, Fusarium sp. and R. stolonifer at 20% concentration. The last one also inhibited by the chemical at 15% concentration. Sodium chloride showed highest 95% inhibition of radial growth of T. viride at 20% concentration. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 11-16, 2017